Program Pengenalan Arab Pegon Pada Usia Dini di TPQ Kanzul ‘Ulum Pogar Tunglur Badas - Mohammad Adi Prasetiyo; Wildan Habibi (LP3M IAIFA Kediri, 2020)
Children are the next generation of nations and religions. Many of their parents want their children to continue their education to boarding schools. Because in the eyes of the wider community education in pesantren is guaranteed if the problem is about religion. In addition, life in boarding schools can also prevent them from falling into an environment that is not expected. The research approach used in this research is the PAR method or Participatory Action Research. With the Research program,